Colour element in children reading book case Study: e-Xra book / Nur Athirah Zulkifi - Zulkifi, Nur Athirah (2019)
Reading is a big part of our lives and it has been taught seen we are little. Reading is important in early-child education for the children. Early-child education or early-child development is actually take places during the children’s brain growth phase. It is important for them to have reading skills, so they can do complex reading when they grow up. But nowadays, the rate of literacy in Malaysia is still low and it is improving but still it did not achieve the target to get 100 per cent in 2020. Children attention also attract to the mobile phone or television more than books as they seem’s more enjoyable than the books. So, this research is to study about colour as it is can attract their attention. The researcher study also about the element of colour and what kind of colour that they like. With this, the publisher can come out with children reading book using colour that recommended. Other than that, the children reading book that were used in this research is e-Xra book. This book actually was used in Dzuliman kindergarten children that in age 4 until 6 years old. The researcher will study the colour that in e-Xra Book by using Newton’s colour theory which is primary colour, secondary colour and tertiary colour. The researcher also were suggested that what kind of colour system that suitable for children reading book and whether the cover of e-Xra book consist that particular colour.